The Notion of Continuing Education in Local Education Reports in Germany-An Analysis of Regional Disparities in Topics, Data, and Governance Recommendations - Pia Gerhards (MDPI AG, 2021)
In Germany, continuing education (CE) is, to a large extent, controlled by municipalities ("Kommunen"). Municipalities have published an increasing number of education reports in recent years. These are intended as steering instruments for local education policy. Given that municipalities and the districts they represent differ in their structures, different challenges and opportunities associated with CE emerge. So far, it remains unclear which aspects of CE are considered by different types of municipalities in their reports and which steering potentials are seen. Based on a content analysis, we present findings on reported topics of CE, the extent of data usage, and derived recommendations for local governance. We separated four district types, showing different degrees of the dimension urban-rural. Although cities published education reports more frequently, rural districts were more likely to address CE issues. However, they had less data available, resulting in a lower range of topics and narrow overall opportunities for addressing CE. Therefore, improvement of data and accessibility of data are important to enhance the monitoring and governance of CE in municipalities. Regarding the reviewed recommendations, clear differences between district types emerged. For instance, expanding offers of CE for immigrants was mainly an issue of large cities, whereas rural districts emphasized the spatial and digital accessibility of offerings.